Prevalence of musculoskeletal disorders in university teachers who perform teletwork in COVID-19 times - García-Salirrosas, Elizabeth Emperatriz (2020)
Introduction. It is estimated that musculoskeletal disorders are the most frequent pathology, affecting the health of teleworkers, productivity in organizations and generating disability. Objective. To determine the prevalence of musculoskeletal disorders and ergonomic risk factors of university professors who teach in the telework modality at different universities in Lima, Peru. Methods. Cross-sectional study. 110 teachers participated in the Kuorinka Nordic questionnaire validated in Peru. Results. The prevalence of musculoskeletal disorders by segment was 100% (n = 110) of the surveyed population. It was found more frequently in the dorso-lumbar spine 67,2% (n = 74) and in the neck 64,5% (n = 71), in a lower percentage in the shoulder 44,5% (n = 49), wrist / hand 38,2% (n = 42) and elbow / forearm 19,1% (n = 21). The teachers associated these musculoskeletal disorders with prolonged postures in the range of 26,8% - 50% and 12,5% - 26,8% with long working hours. The majority age group was 39,1% (n = 43) from 41 to 50 years and 28,2% (n = 31) from 31 to 40 years. 70,9% (n = 78) were men and 29,1% (n = 32) were women. Conclusion. There is a high prevalence of musculoskeletal disorders in university teachers, mainly in the dorsal-lumbar spine and neck; and there is an association of these disorders with ergonomic risk factors such as prolonged posture and long working hours.